2009
DOI: 10.1016/j.jsbmb.2009.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Assisted reproduction technologies impair placental steroid metabolism

Abstract: The placenta plays a vital role in pregnancy by facilitating steroid passage from maternal to fetal circulation and/or direct production of hormones. Using a murine model, we demonstrated the differences in placental steroid metabolism between pregnancies conceived naturally and with assisted reproduction technologies (ART): in vitro fertilization (IVF) and intracytoplasmic sperm injection (ICSI). While the ovarian steroid production was similar (estrone, 17β-estradiol) or higher (estriol) in ART pregnancies c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
44
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 37 publications
6
44
0
2
Order By: Relevance
“…In particular for reproduction, UGT1A1 is known to metabolize estrogenic hormones, thereby terminating estrogen actions and facilitating elimination of the steroid. Our own laboratory has demonstrated assisted reproduction technologies in the mouse model alter steroid glucuronidation at the level of the placenta, in part through transcriptional induction of Ugt1a genes (Collier et al 2009, 2012; Raunig et al 2011). Moreover, we and others have demonstrated that UGT isoform expression is tissue specific and transcription, as well as activities, can be related to levels of sex steroids (Buckley and Klaassen 2007, 2009; Collier et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular for reproduction, UGT1A1 is known to metabolize estrogenic hormones, thereby terminating estrogen actions and facilitating elimination of the steroid. Our own laboratory has demonstrated assisted reproduction technologies in the mouse model alter steroid glucuronidation at the level of the placenta, in part through transcriptional induction of Ugt1a genes (Collier et al 2009, 2012; Raunig et al 2011). Moreover, we and others have demonstrated that UGT isoform expression is tissue specific and transcription, as well as activities, can be related to levels of sex steroids (Buckley and Klaassen 2007, 2009; Collier et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Hence glucuronidation primarily develops in the postnatal period, independent of gestational age at birth (Burchell et al 1989; Coughtrie et al 1988; Kawade and Onishi 1981; Strassburg et al 2002). Thus, during pregnancy UGT1A isoforms seem to be important for balancing maternal–placental–fetal homeostasis, fetal development and regulating chemicals, nutrients and waste exposure (Collier et al 2004, 2009; Ginsberg and Rice 2009; Raunig et al 2011; Reimers et al 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Arylsulfatase C activity was determined as previously described using the substrate p -nitrophenyl sulfate (Collier et al, 2009; Sugawara et al, 2012). Absorbance was measured at λ = 420 nm for 45 min.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have shown that ART increases term placental weight in mice (1015). Intriguingly, the procedure of transferring blastocyst stage embryos alone can increase overall placental weight, strongly sμggesting that relatively brief procedures can contribute to placental phenotypes (14).…”
Section: Assisted Reproductive Technology (Art) As An Environmental Ementioning
confidence: 99%
“…In human ART placenta, proteome analyses identified genes associated with membrane traffic, metabolism, nucleic acid processing, stress response, and cytoskeletal functions (12). Also, ART placentas have been shown to have significantly higher steroid metabolizing enzyme activity, resulting in a higher clearance capability (10,42). Althoμgh not entirely clear, this may impact hormone signaling and fetal growth.…”
Section: Assisted Reproductive Technology (Art) As An Environmental Ementioning
confidence: 99%